Schizophrenia spectrum stigma in healthcare: a systematic review - Elizabeth A. Kruse; David Dodell-Feder; David Dodell-Feder (Frontiers in Psychiatry)
IntroductionWithin healthcare settings, schizophrenia spectrum disorder (SSD) stigma is pervasive and presents significant barriers to recovery and equitable care. Understanding the sources, nature, and moderators of such stigma among healthcare providers is essential for informing targeted interventions.MethodsWe conducted a systematic review of 44 peer-reviewed studies examining SSD-related stigma among diverse healthcare providers, including trainees, nurses, general practitioners, psychiatrists, psychologists, and community health workers. Studies were synthesized to identify common manifestations of stigma, as well as professional and demographic moderators.ResultsStigma was observed across all healthcare professions, manifesting through stereotypes, prejudices, and discriminatory behaviors. Consistent patterns included higher stigma among generalist providers compared to mental health specialists and reduced stigma associated with greater professional experience and personal contact with individuals with SSDs. Findings regarding other moderators, such as age, gender, and etiological beliefs, were mixed.DiscussionSSD stigma is widespread within healthcare and varies by provider type, training, and personal experience. Interventions to reduce stigma should be tailored to specific provider groups and contexts. Future research should employ longitudinal and mixed-method designs to clarify moderator effects and assess targeted anti-stigma strategies.